Executive dysfunctions impair and levodopa improves articulatory timing in Parkinson‘s disease - Herbig, Elisa; Mücke, Doris; Barbe, Michael T.; Thies, Tabea (Frontiers in Human Neuroscience, 2025)
This study investigates the effects of executive functions and levodopa on articulatory timing patterns in simple and complex syllable onsets (CV vs. CCV) in Parkinson’s disease (PD). Kinematic speech data (EMA) of 25 individuals with PD in medication-OFF as well as medication-ON condition and 25 healthy controls (HC) were recorded, and group differences were examined. Results showed preserved articulatory coordination that is skewed in time in the PD group as well as a positive effect of levodopa on these patterns. Cluster analysis revealed an age-dependent decline in executive functions across groups that correlated with the shift pattern of the second consonant in CCV sequences for the PD group. This indicates that executive dysfunctions could give rise to changes in articulatory timing patterns as the disease progresses but independently of general motor severity.